Agentes etiológicos aislados en las infecciones bacterianas y su perfil de susceptibilidad en pacientes con neoplasias hematológicas y trasplante de progenitores hematopoyéticos del Hospital Nacional Edgardo Rebagliati Martins - Avalos Valdez, Astrid Carolina (2019)
The objective of this report was to identify the etiological agents in bacterial infections and their antibiotic susceptibility profile in patients with hematological malignancies and hematopoietic stem cell transplantation of the Edgardo Rebagliati Martins National Hospital. The study consisted of 48 patients hospitalized during the period between March - August 2017 in the Hematology service (8C) and Bone Marrow Transplant (8A - 8C T). For the identification of the etiological agents and their antibiotic susceptibility profile, the data were collected from the antibiogram reports of the clinical histories that showed positive cultures to bacterial infections. Where Gram negative bacteria (81.25%) and Gram positive bacteria (18.75%) were identified. Of which the microorganisms most frequently isolated was Escherichia coli ESBL+(31.25%) followed by Escherichia coli (25%),Klebsiella pneumoniae (12.50%),Pseudomonas aeruginosa (10.42%). Regarding the susceptibility pattern, these microorganisms showed sensitivity to merepem, imipenen, piperacillin / tazobactan and a percentage of resistance to the group of cephalosporins. It was also identified that the most frequent infectious focus was the skin (61%) and the cultivated samples were taken with greater frequency of the central venous catheter with a total of 35.42%. It is concluded that bacterial infections in patients with hematological malignancies and haematopoietic stem cell transplantation are more frequently associated with Gram negative bacteria compared to Gram positive bacteria